Dilema Wakaf Timur Kuran Perspektif Maqashid Al-Shari'ah - Dwi Aprilianto (JES (Jurnal Ekonomi Syariah), 2018)
Waqf is an established institution in Islamic religion, and belongs to the category of community worship whose position is very important as capital and means in achieving the welfare of the people. However, in practice there have been many deviations from the origin of the purpose of waqf. Therefore, a new orientation on waqf is needed, so that waqf can contribute effectively to the welfare of the people. It must meet four factors including, legal certainty status, right and proper pledge of waqf, effective management of waqf. The importance of waqf development certainly has implications on how the management of waqf in providing utilization for the community. Waqf management is required to be professional, trustworthy, transparant, and accountable. This article explains the criticism of Timur Kuran’s dilemma about the waqf system which is a lot of deviation from the goal of essensial waqf.  Therefore, a new orientation on waqf is required, so that waqf can contribute effectively to the welfare of the people. But in the other hand, Kuran does not offer concrete solutions or create a theory about the norms of Islamic economic activity to replace or revise the norms put forward by Islamic economists. To be a criticism of the dilemma, this article also sees from the side of maqashid al-shari’ah in waqf also oriented to the present interest for the achievement of development social-oriented productive property, and the result will also be felt together by maslahah ‘ammah community. Kuran based his view of the unbelievable sources of the orientalists. As Kuran believes, Islamic economics is a fundamentalistist doctrine, rigid, rigid and only excavated from traditional Islamic sources. Keywords: Timur Kuran, Waqf, Maqashid al-Shari’ah Perspective